2005
DOI: 10.1242/jcs.01639
|View full text |Cite
|
Sign up to set email alerts
|

Migfilin and its binding partners: from cell biology to human diseases

Abstract: Links between the plasma membrane and the actin cytoskeleton are essential for maintaining tissue integrity and for controlling cell morphology and behavior. Studies over the past several decades have identified dozens of components of such junctions. One of the most recently identified is migfilin, a widely expressed protein consisting of an N-terminal filamin-binding domain, a central proline-rich domain and three C-terminal LIM domains. Migfilin is recruited to cell-matrix contacts in response to adhesion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
73
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 47 publications
5
73
0
Order By: Relevance
“…Sahai and Marshall have shown that the protease-independent amoeboid mode of invasion is enhanced by Rho signaling (1). It is worth noting that Mig-2 interacts with h integrins and promotes focal adhesion formation (20)(21)(22)(23), a process that is known to involve Rho signaling. Thus, it will be interesting to test in future studies whether Mig-2 promotes the protease-independent cancer cell invasion through regulation of Rho signaling.…”
Section: Mig-2 Inhibits Pericellular Proteolytic Activity Of Sk-lms-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Sahai and Marshall have shown that the protease-independent amoeboid mode of invasion is enhanced by Rho signaling (1). It is worth noting that Mig-2 interacts with h integrins and promotes focal adhesion formation (20)(21)(22)(23), a process that is known to involve Rho signaling. Thus, it will be interesting to test in future studies whether Mig-2 promotes the protease-independent cancer cell invasion through regulation of Rho signaling.…”
Section: Mig-2 Inhibits Pericellular Proteolytic Activity Of Sk-lms-1mentioning
confidence: 99%
“…Mitogen inducible gene-2 (Mig-2, also known as kindlin-2) is an integrin-binding scaffolding protein that is concentrated at the intracellular face of cell-ECM adhesions, where it links integrins to the actin cytoskeleton (20)(21)(22)(23). Recent studies have shown that Mig-2 is highly expressed in aggressive human TMX2-28 breast cancer cells (24).…”
Section: Introductionmentioning
confidence: 99%
“…The connection between the extracellular matrix (ECM) and adjacent cells plays a significant role in cell fate determination, including differentiation, proliferation, migration and apoptosis [4] . Filamin binding LIM protein 1 (FBLIM1), also known as migfilin, is characterized as a skeleton organization protein that binds to mitogen-inducible gene 2 (Mig-2) at cell-ECM adhesions [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…The C-terminal region has three sequential LIM domains [8] . In addition, two types of migfilin isoforms have been differentiated as migfilin(s) and FBLP-1 [4,8] . Migfilin(s) is a splicing variant with a proline-rich region deleted, resulting in the loss of the VASP binding site [4,5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation